The Role of Land Management Paradigm Towards Certainty and Justice - Setiabudhi, Donna Okthalia; Yunus, Ahsan; Irwansyah, Irwansyah; Rifky, Andi (BESTUUR, 2023)
To achieve land order, Indonesia implements the Sustainable Agrarian Regulation System (SPAB). The crucial issue, however, is whether the management of activities at this point has been conducted sustainably in order to establish justice and legal certainty in the community.   The purpose of this study is to examine a variety of issues concerning the Role of Land Management Paradigm Towards Certainty and Justice. This research is empirical with a qualitative approach. The results indicate that as the Dynamics of Population Growth and Rapid Progress was being constructed, soil quality began to deteriorate. For the exploitation and utilization of soil, therefore, effective, efficient, and sustainable land management is necessary.  It is widely acknowledged that sustainable land management is essential for halting land degradation, preventing desertification, and regenerating degraded areas. Given the complex options available to communities and landowners, Japan's policy is shifting its emphasis to policies pertaining to sustainable land use management by means of consensus building.